Akuntansi Lingkungan Berbasis Ekosistem Pesisir: Integrasi Valuasi Karbon Biru ke dalam Kerangka Pelaporan Korporat dan Kebijakan Iklim di Indonesia dan Malaysia - Risa Rukmana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2026)
Blue accounting requires more than just the technical capabilities to measure, report and verify coastal carbon stocks. The success of blue accounting depends on good governance, institutional readiness, and integration with carbon market mechanisms. In this article, a thorough literature review is provided. This review looks at aspects of governance, policy and economic valuation that influence the implementation of blue accounting in Indonesia and Malaysia. This study, using the PRISMA 2020 framework and analyzing fourteen articles that met the inclusion criteria, found that both countries face similar but different problems in institutional structures, legislative readiness, and data integration into carbon market mechanisms. Technical capacity to estimate carbon and active implementation of REDD+ policies are Indonesia's main strengths; however, there is still little standardization of blue accounting at the company level. Institutional organization in Malaysia is more organized than in other countries. However, uncertainty about land ownership rights and a lack of financing mechanisms hinder the effective implementation of blue accounting. This study helps build a more consistent and functional blue carbon accounting governance framework in Southeast Asia. This has a direct impact on coastal conservation policies, corporate sustainability reporting, and the growth of regional carbon markets.